Quartz-Enhanced Photoacoustic Spectroscopy for Four-Component Gas Detection Based on Two Off-Beam Acoustic Microresonators - Wang, Cheng; Wang, Zongliang; Pang, Xiyu (Frontiers in Physics, 2020)
A compact and portable quartz-enhanced photoacoustic spectroscopy gas sensor was developed for four-component gas detection using two off-beam acoustic microresonators (AMRs). The two AMRs were placed in parallel on opposing sides of a quartz tuning fork (QTF) for photoacoustic signal enhancement. Four distributed feedback (DFB) lasers were connected to the four ends of the two off-beam AMRs using a fiber collimator for photoacoustic signal excitation. Four-component gas sensing was achieved via time-division multiplexing of the DFB laser driver currents. The four-component gas sensing scheme was used to detect acetylene (C2H2) at 1532.83 nm, methane (CH4) at 1653.722 nm, water vapor (H2O) at 1368.597 nm and carbon dioxide (CO2) at 1577.787 nm for feasibility testing. Minimum detection limits of 3.6 ppmv for C2H2, 34.71 ppmv for CH4, 1.09 ppmv for H2O, and 341.18 ppmv for CO2 were obtained, and the linear responses reached 0.9982, 0.9969, 0.99843 and 0.99591 for C2H2, CH4, H2O and CO2, respectively, at 1.5 s intervals.